O centro da cidade e as novas áreas de centralidade na cidade média de Juazeiro do Norte/CE - Pereira, Cláudio Smalley Soares [UNESP] (My University, 2015)
This paper discusses the urban centrality redefinition on the city scale. The Juazeiro do Norte city in the Ceará State - Brazil, was the study object and the conceptual questions regarding the central urban areas, and the new areas emergence concentration of trade and services beyond the downtown from three specific economic activities are addressed: appliance stores, super and hypermarkets (associated with shopping centers or not), and banks. These new areas express different centralities and maintain various relationships with the downtown and central urban areas. These relationships, which are seized from the spatial practices of urban people related to consumption, which ultimately prioritize and articulate any differents spaces according to their needs. The research revealed that the new locational logic of commerce and services in the municipality of Juazeiro do Norte keeps the same logic as many other medium-sized cities in Brazil, with economic agents playing an important role in the process of transformation and expansion in the city. The closing of many shops in the center of the city occurred with the increase in urban land prices and showed that this process is the result of capitalist production in the city and the logic the use of urban space has en structured in recent decades. We concluded that urban space Juazeiro is restructured from the location strategies of enterprises expressing centrality to the entire city and beyond, such as shopping malls and hypermarkets, providing changes in spatial practices.
The centre and new areas of centrality in the mid-sized city of Juazeiro do Norte/CE
Keywords: Production of urban space; Restructuring the city; Tertiary sector